2018
DOI: 10.1002/jcp.27105
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA DSCAM‐AS1 acts as a sponge of miR‐137 to enhance Tamoxifen resistance in breast cancer

Abstract: LncRNA DSCAM-AS1 acts as a competing endogenous RNA of miR-137 and regulates EPS8 to promote cell reproduction and suppresses cell apoptosis in TR breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 34 publications
1
41
0
Order By: Relevance
“…Recently studies showed that miR-137 might participate in the progression of CRC by directly targeting at EZH2 [32], TCF4 [31] and YBX1 [33]. Study showed that DSCAM-AS1 may act as a competing endogenous RNA of miR-137 and regulates EPS8 to promote cell reproduction and suppresses cell apoptosis in TR breast cancer [34]. RT-qPCR results in our study displayed that the expression of miR-137 in CRC tissues was relatively lower than that in normal tissues, and was negatively correlated with the expression of DSCAM-AS1.…”
Section: Discussionmentioning
confidence: 99%
“…Recently studies showed that miR-137 might participate in the progression of CRC by directly targeting at EZH2 [32], TCF4 [31] and YBX1 [33]. Study showed that DSCAM-AS1 may act as a competing endogenous RNA of miR-137 and regulates EPS8 to promote cell reproduction and suppresses cell apoptosis in TR breast cancer [34]. RT-qPCR results in our study displayed that the expression of miR-137 in CRC tissues was relatively lower than that in normal tissues, and was negatively correlated with the expression of DSCAM-AS1.…”
Section: Discussionmentioning
confidence: 99%
“…The Down syndrome cell adhesion molecule antisense RNA 1 (DSCAM-AS1) is an intronic antisense lncRNA that is transcribed from the opposite strand of the Down syndrome cell adhesion molecule (DSCAM) gene, and is wholly derived from the intronic region of DSCAM. DSCAM-AS1 promotes tamoxifen resistance [110,111] and is upregulated in breast cancer tissues compared with normal tissues [110,112]. Moreover, DSCAM-AS1 expression is higher in luminal and HER2-positive breast cancers, and particularly in the luminal B subtype [110,112].…”
Section: Lncrnas Belonging To Multiple Categoriesmentioning
confidence: 99%
“…68 TINCR sponges miR-125b and promotes TZB resistance in HER-2+ BC cells. 100 Other lncRNAs such as FTH1P3, 67 LINC00511, 69 ATB, 103 CYTOR, 81 DSCAM-AS1, 83,84 ROR, 86 ADAMTS9-AS2, 91 LINC00894-002, 92 NONHSAT101069, 29 and PRLB 77 sponge specific miRNAs to regulate drug resistance in BC.…”
Section: Cernasmentioning
confidence: 99%